Un programa de intervención para prevención y tratamiento del absentismo escolar en Primaria - Garfella Esteban, Pedro R. (2000)
We elaborated and applied a training programme to prevent and treat the students absenteeism in the school children in Primary Level in a middle-sized city in Spain. We succeeded in increasing the presence of the students with absences in the school and also in improving their self-esteem. This programme was conducted by the investigators and was developed by a well-coordinated team: the headship, the teachers, the pedagogue, the social worker and so on.